PKM Development of IoT-Based Sensor Trainers for Teachers of SMKN 1 Takalar to Support Distance Learning - Nuridayanti; Purnamawati; Muhammad Akil; Usman Mulbar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This PKM activity aims to increase teachers' understanding and skills of IoT technology in distance learning, introduce sensor and transducer trainers that can be used in remote practicums using IoT, and provide training on using IoT trainers for teachers at SMKN 1 Takalar. This service activity was carried out at SMKN 1 Takalar. The method for implementing PKM activities is divided into three stages, namely, Activity Planning, Implementation Stage and Evaluation Stage. The results of the participants' instruments with questions The material presented was clear and easy to understand. The conclusion from the results of the PkM activity instrument analysis illustrates that the PkM activities that have been carried out are in accordance with the needs and solutions for solving problems experienced by partners